Analysis of the Effects of Energy Consumption, Employment, Mining, Natural Resource Income, and Foreign Direct Investments on Economic Growth in the Central Asian Turkic Republics Using Panel Causality Tests - Baimagambetova, Lyazzat; Baibulekova, Lyailya; Aliyeva, Zhanna T.; Aidarova, Aina Bailarovna; Mashirova, Tazhikul; Balapanova, Elmira; Nurpeissova, Aigul; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of energy consumption, employment, mining and natural resource revenues, and foreign direct investments on economic growth in the Central Asian Turkic Republics, specifically Azerbaijan, Kazakhstan, Kyrgyzstan, Turkmenistan, and Uzbekistan. A panel data analysis was conducted using annual data covering the period from 1993 to 2023. The relationship between the variables was investigated using the Dumitrescu- Hurlin panel causality test, while the Hsiao homogeneity test confirmed that the series were homogeneous. The findings indicate that foreign direct investments (FDI) have a one-way causal effect on economic growth and that these investments also lead to increased energy consumption. Conversely, no direct impact of energy consumption, employment, or natural resource revenues on economic growth was observed. While periodic fluctuations in energy consumption and natural resource revenues were noted among the countries, economic growth exhibited a more stable trajectory, particularly after 2000. These results highlight the critical role of foreign direct investments in fostering sustainable growth and underscore the importance of channeling these investments into the production sector. It is recommended that policymakers devise long-term strategies for energy and investment that will promote economic stability and growth.